Characteristics of metabolites analysis for patients with granulomatous lobular mastitis - Dai, Qiuying; Zhou, Yue; Wu, Jingjing; Liao, Mingjuan (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundGranulomatous lobular mastitis (GLM) is a type of non-puerperal mastitis (NPM) associated with autoimmune factors. Previous studies suggest that gut microbiota dysbiosis may play a role in the pathological process of GLM; however, the specific role of gut microbiota metabolites in this process remains unclear. Therefore, this study aimed to investigate the gut metabolic characteristics of short-chain fatty acid (SCFA) in patients with GLM, a type of NPM.MethodsStool samples were collected from 35 patients with GLM and 26 healthy control (HC) subjects. These samples underwent targeted metabolomic analysis to measure SCFA and 16s rRNA high-throughput sequencing to assess gut microbiota composition and differences between the groups.ResultsGas chromatography-mass spectrometry(GC-MS) analysis revealed that the content of SCFA-butanoic acid in the feces of patients with GLM was higher than that in the HC group. Notably, significant differences in metabolic pathways were observed between the HC and GLM groups. High-throughput sequencing results showed that the richness and diversity of gut microbiota in patients with GLM were significantly lower than those in healthy individuals. In addition, 53 bacterial species were found to differ significantly in abundance between the two groups. Moreover, the level of isohexanoic acid in the feces of patients with GLM with recurrence disease was significantly higher than that of patients without recurrence.ConclusionsPatients with GLM exhibit disturbances in gut butanoic acid metabolism and significant differences in gut microbiota structure compared to healthy individuals.